2021
DOI: 10.3390/w13081030
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Transport in a Lowland Stream Derived from a Tracer Test with 32P

Abstract: Small streams in urbanized rural areas receive loads of P from various, often episodic, sources. This paper addresses, through a tracer test with 32P, retention and transport of a pulse input of phosphorus in a 2.6 km long stretch of a channelized second-order lowland stream. Tritiated water was introduced alongside the 32P-labelled ortophosphate in order to isolate the influence of the hydrodynamic factors on P behavior. Tracer concentrations in unfiltered water samples were measured by liquid scintillation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…(2017) studied the contributions of dissolved phosphorus from hyporheic exchange and groundwater to lake eutrophication. Zieba and Wachniew (2021) found that the overall retention efficiency of 32 P was 46% in a lowland stream in a tracer test. Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…(2017) studied the contributions of dissolved phosphorus from hyporheic exchange and groundwater to lake eutrophication. Zieba and Wachniew (2021) found that the overall retention efficiency of 32 P was 46% in a lowland stream in a tracer test. Li et al.…”
Section: Introductionmentioning
confidence: 99%